The labor market in Sweden since the 1990s - Nils Gottfries (IZA World of Labor, 2018)
The economic crisis in the early 1990s brought about a dramatic increase in unemployment and a similar decrease in labor force participation. Unemployment declined afterwards, but stabilized at around 6–7%—more than twice as high as before the crisis. Today, the unemployment rate is lower than the EU average, though Sweden no longer stands out in this respect. The 2008 financial crisis had small effects on the Swedish labor market. Employment in industry declined sharply and then remained stagnant, but employment in the service sectors has continued to grow steadily.
Keywords: E24; J3; J6; 330; unemployment; employment; labor force participation; wage inequality